Comparative analysis of intercultural education from the perspective of management teams. The case of spain and france - Sevillano-Monje, Verónica; Martín-Gutiérrez, Ángela; León-Sánchez, Mario (Croatian Journal of Education, 2024)
The right to education for all people has been recognised worldwide for decades. Because of this, educational organisations and management teams, through pedagogical leadership, must work towards the construction of inclusive and intercultural schools that generate a plural, collaborative, and democratic space. Therefore, this research aims to analyse the importance of the role of management teams in the promotion of intercultural education in schools in Spain and France. To achieve the stated objective, a documentary analysis of the educational legislation of reference and international reports was carried out. The following indicators were compared: leadership of the management team, collaborative culture, self-efficacy, innovation, and educational practices related to cultural diversity. High rates of innovation and internal collaborative culture are evident in both countries. However, the data show that the management teams do not promote relations with the environment. Therefore, there is a need for better and continuous training of management and teaching staff in the promotion of equity and cultural diversity. In addition, the lack of training in pedagogical leadership within the French management team is highlighted. Following the results obtained, the transformation of schools requires enabling the creation of a collaborative culture that involves the educational community and the environment. To this end, it is necessary to provide initial and continuous training for the management team and teachers in intercultural competencies.
Usporedna analiza međukulturnoga obrazovanja iz perspektive upravljačkih timova. Slučaj španjolske i francuske
Pravo na obrazovanje za sve ljude već je desetljećima priznato u cijelome svijetu. Zbog toga obrazovne organizacije i upravljački timovi moraju putem pedagoškoga vodstva raditi na izgradnji inkluzivnih i međukulturnih škola koje stvaraju pluralni, suradnički i demokratski prostor. Stoga je cilj ovoga istraživanja analizirati važnost uloge upravljačkih timova u promicanju međukulturnoga obrazovanja u školama u Španjolskoj i Francuskoj. Kako bi se postigao navedeni cilj, provedena je analiza referentnih dokumenata obrazovnoga zakonodavstva i međunarodnih izvješća. Uspoređeni su sljedeći pokazatelji: vodstvo upravljačkoga tima, kultura suradnje, samoučinkovitost, inovativnost i obrazovne prakse povezane s kulturnom raznolikošću. Visoke stope inovacija i interne kulture suradnje vidljive su u obje zemlje. Međutim, podatci pokazuju da upravljački timovi ne promiču odnose s okolinom. Stoga postoji potreba za boljom i kontinuiranom izobrazbom upravljačkoga i nastavnoga osoblja u promicanju pravednosti i kulturne raznolikosti. Osim toga, ističe se nedostatak obuke u pedagoškom vodstvu francuskoga upravljačkoga tima. Slijedom dobivenih rezultata, transformacija škola zahtijeva omogućavanje stvaranja suradničke kulture koja uključuje obrazovnu zajednicu i okolinu. U tu svrhu potrebno je osigurati početno i kontinuirano osposobljavanje upravljačkoga tima i nastavnika u području međukulturnih kompetencija.
Keywords: pedagogical leadership; intercultural education; documentary analysis; management teams